Assessing the Static and Dynamic Sensitivity of a Commercial Off-the-Shelf Multicore Processor for Noncritical Avionic Applications - Pablo F. Ramos; Vanessa C. Vargas; Nacer-Eddine Zergainoh; Raoul Velazco (Journal of Nanotechnology)
The present work assesses the radiation sensitivity of an affordable and performant COTS multicore processor for noncritical avionic applications. The target device is the Epiphany E16G301 multicore manufactured in 65 nm CMOS which integrates 16 processor cores. This device was selected due to its high performance, low power consumption, and affordability, allowing general public accessing to parallel computing. Additionally, the E16G301 is the coprocessor for parallel processing of the Parallella platform, which was considered by NASA researchers for onboard health management of the DragonEye UAS. The evaluation of the device is done using quantitative theory by means of radiation experiments with 14 MeV neutrons to emulate the effects of high-energy neutrons present at avionic altitudes. Static and dynamic cross sections are obtained to evaluate the intrinsic sensitivity of the device as well as its dynamic response. Results show that the failure rate of the E16G301 running a matrix multiplication as application reaches level D of the DO-178B/C guideline, being the device well suited for minor failure conditions of avionic applications.